PERBEDAAN HASIL UJI KOAGULASE MENGGUNAKAN PLASMA SITRAT MANUSIA 3,8%, PLASMA SITRAT DOMBA 3,8%, DAN PLASMA SITRAT KELINCI 3,8% PADA BAKTERI Staphylococcus aureus - Yunan Jiwintarum; Lalu Srigede; Auliya Rahmawati (Jurnal Kesehatan Prima, 2015)
Abstract: Coagulase test is a bacterial examination performed to detect the formation of coagulase enzyme bound to the bacterial cell wall. This study aims to determine the difference in the form of a coagulase test results clot formation by using several types of plasma citrate in bacteria Staphylococcus aureus. This type of research is true experimental replication using 9 and 3 human citrate plasma treatment is 3.8%, 3.8% sheep plasma citrate, and 3.8% rabbit citrate plasma. The results show the average time of the formation of clots in the coagulase test using 3.8% human citrate plasma was 1:29 minutes, using sheep plasma citrate 3.8% was 00:54 minutes, and using 3.8% rabbit citrate plasma is 1:40 minutes. Results of One Way Anova statistical test obtained p value count (0,00) <p α (0.05), meaning that there are significant differences in the results of coagulase test using human plasma citrate 3.8%, 3.8% sheep plasma citrate, and rabbit plasma citrate 3.8% in Staphylococcus aureus.